The influence of organic and conventional crop management, variety and year on the yield and flavonoid level in common buckwheat groats - Kalinova, Jana; Vrchotova, Nadezda (Food chemistry, 2011)
Common buckwheat (Fagopyrum esculentum Moench) is a pseudocereal that is cultivated for its achenes that possess a high level of flavonoids. Some scientific studies have found that the growing conditions can significantly affect the flavonoid content in conventional and organic food products. Hence, the present study compared conventionally and organically produced common buckwheat with respect to the content of selected flavonoids, thousand achenes weight and achene yield. Three buckwheat varieties were grown with organic and conventional crop management under the same environmental conditions. The thousand achenes weight and achene yield were not significantly influenced by way of crop management. The level of rutin, epicatechin, catechin, and epicatechin gallate in buckwheat groats (hulled achenes) were quantified with high pressure liquid chromatography. Only rutin and epicatechin gallate reached significantly higher level in organic groats. However, the differences were influenced by environmental conditions in the given year and variety.